2020
DOI: 10.1111/jocd.13810
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of topical tranexamic acid (liposomal or lotion with microneedling) versus conventional hydroquinone in the treatment of melasma

Abstract: Background Robust evidence regarding the efficacy of topical tranexamic acid (TA) on melasma in Chinese population is lacking. Objective To evaluate the efficacy and safety of 1.8% liposomal TA and microneedling with 5% TA solution on melasma. Methods Sixty melasma patients were enrolled and randomized to receive 1.8% liposomal TA twice daily, microneedling with 5% TA solution weekly or 2% hydroquinone every night. Objective and subjective assessments were obtained at baseline, 4, 8, and 12 weeks. Results 27.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Given that microneedling has an added cost and requires more frequent office visits, the authors suggest that patients may be more adherent to topical HQ treatment. 33 Vitamin C is another compound that interferes with melanin formation and has been used to decrease hyperpigmentation.…”
Section: Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Given that microneedling has an added cost and requires more frequent office visits, the authors suggest that patients may be more adherent to topical HQ treatment. 33 Vitamin C is another compound that interferes with melanin formation and has been used to decrease hyperpigmentation.…”
Section: Evidencementioning
confidence: 99%
“…They also found that the TXA formulations were better than the HQ treatment at reducing inflammation as shown by the erythema index. Given that microneedling has an added cost and requires more frequent office visits, the authors suggest that patients may be more adherent to topical HQ treatment 33 …”
Section: Introductionmentioning
confidence: 99%
“…Microneedles are applied to the skin with the drugs can not only transport active ingredients through the stratum corneum, but also generates multiple micropunctures with bleeding, which could stimulate the wound‐healing response, thereby initiating neocollagenesis and neo‐elastogenesis 40,41 . Two studies 37,42 demonstrated that microneedling with 5% TXA improves pigmentation and erythema, presented as significantly smaller melanin index (MI) and erythema index (EI), bigger improvement in physician assessments, and higher patient satisfaction with minimal side effects. Cassiano et al 40 compared microneedling with oral TXA and other treatments, demonstrating that TXA and microneedling act through two distinct pathways to alleviate melasma, with microneedling providing longer‐lasting remission than standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…12,39 Microneedles are applied to the skin with the drugs can not only transport active ingredients through the stratum corneum, but also generates multiple micropunctures with bleeding, which could stimulate the wound-healing response, thereby initiating neocollagenesis and neo-elastogenesis. 40,41 Two studies 37,42 providing longer-lasting remission than standard therapy. In order to increase the drug concentration at target melanosomal cells in the stratum basal layer of the epidermis and decrease incidence of adverse events, more and more novel microneedles, such as liposomes, trans-ethosomes, biocompatible polymers, and dissolving microneedles have been explored and developed.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…However, due to its hydrophilic structure, TA is unable to permeate skin passively. Therefore, enhancement techniques such as liposomes or physical modalities (microneedling, lasers) are required to assist transdermal TA delivery [ 8 14 ].…”
Section: Introductionmentioning
confidence: 99%